Analisis Keterlambatan Penyelesaian C-check: Delay Maintenance - Martina, Ayu; Suwondo, Edy; Yuniarti, Endah (Jurnal Teknologi Kedirgantaraan, 2023)
PT XYZ is one of the air transportation companies in Indonesia that experienced delays in completing C-check maintenance based on a predetermined schedule. The TAT (Turn Around Time) indicator is used to measure the performance in completing the maintenance at PT XYZ. This research aims to determine the factors that cause maintenance delays on the B737NG aircraft and minimize TAT delays. This research uses fishbone diagrams and Pareto diagrams to find the root causes. There are three main factors that cause the delays, namely due to lack of manpower, the process of waiting for material supply, and the length of time to process the findings. In order to strengthen the analysis, this research uses the Define Measure Analyze Improve Control (DMAIC) method with the support of FMEA to develop a table for the RPN values or risk priority scale. The calculation results show that the highest RPN value is not paying attention on the ratio of work to manpower, which gives an RPN value of 216. Then a solution is recommended to reduce the RPN value to become value 168 where the aim is to reduce the TAT delay in completing the C-check maintenance of PT XYZ’s Boeing 737NG aircraft.